Impact of improving community-based access to malaria diagnosis and treatment on household costs - Castellani, J; Nsungwa-Sabiiti, J; Mihaylova, B; Ajayi, I; Siribié, M; Afonne, C; Balyeku, A; Sermé, L; Sanou, A; Sombié, B; Tiono, A; Sirima, S; et al. (Oxford University Press, 2016)
Background: Community health workers (CHWs) were trained in Burkina Faso, Nigeria and Uganda to diagnose febrile children using malaria rapid diagnostic tests (RDTs), treat positive malaria cases with artemisinin combination treatment (ACTs) and those who could not take oral medicines with rectal artesunate. We quantified the impact of this intervention on private household costs for childhood febrile illness. Methods: Households with recent febrile illness in a young child in previous two weeks were selected randomly before and during the intervention and data obtained on household costs for the illness episode. Household costs included consultation fees, registration costs, user fees, diagnosis, bed, drugs, food and transport costs. Private household costs per episode before and during the intervention were compared. The intervention’s impact on household costs per episode was calculated and projected to district-wide impacts on household costs. Results: Use of CHW increased from 35% of illness episodes before the intervention to 50% during the intervention (p<0.0001) and total household costs per episode decreased significantly in each country from 4.36 to 1.54 dollars in Burkina Faso, from 3.90 to 2.04 dollars in Nigeria and from 4.46 to 1.42 in dollars Uganda (all p<0.0001). There was no difference in the time used by the child’s caregiver to care for a sick child (59% before intervention vs. 51% during intervention spent 2 days or less). Using the most recent population figures for each study district, we estimate that the intervention could save households a total of 29,965, 254,268 and 303,467 dollars, respectively in the study districts in Burkina Faso, Nigeria and Uganda. Conclusions: Improving access to malaria diagnostics and treatments in malaria endemic areas substantially reduces private household costs. The key challenge is to develop and strengthen community human resources to deliver the intervention, and ensure adequate supplies of commodities and supervision. We demonstrate feasibility and benefit to populations living in difficult circumstances.